Electromagnetic Transition Strengths in110Cd Nucleus - Jassim, Fatima (Iraqi Journal of Science, 2024)
Pure transition strengths [M(E1)]2W.u,[M(E2)]2W.uand [M(M1)]2W.u for /-transitionsfrom four excited states in 110Cd populated in the 108Pd (2,2n) reaction have been studiedthrough the mean life times with relative intensities of /- transitions measurements.Good information describes the main features of the transition modes for electricquadrupole [M(E2)]2W.u and electric dipole [M(E1)]2W.u in addition to magnetic dipole[M(M1)]2W.u are concluded .PACS:- 27.60-j, 23.20-g, 23.20.Ck, 23.20.Gq.